Rancang Bangun Ekonomi Islam Adiwarman Karim dalam Kajian Epistomologi Islam - Shafrani, Yoiz Shofwa (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
The development of Islamic economic thought in Indonesia is still considered only in the banking and financial sector. So, necessary a process to be able to unify the concept of Islamic values ​​and economic concepts so that the Islamic economy can unite at the empirical level. It is hoped that the integration between Islamic values ​​and economic values ​​can broadly describe the concept of Islamic economics. This process can be successful if it is supported by the instruments, especially humans as the main instrument. One of the figures of Islamic economic thought who integrates theory and practical level is Adiwarman Karim. It offers the concept of Islamic economics in all aspects and fields of Islamic economics and business. The thought structure adopted by him is fundamentalist-intellectual-professional, so the concept of Islamic economics offered is the design of Islamic economics. Epistomologically, the background behind Adiwarman getting this idea is based on formal education and the practical world. The methods of obtaining knowledge are historical, fiqh and economic approaches. Then for the contribution of thought seen in the concept of monetary, a good competitive, foreign exchange control and inflation, money, zakat, Islamic banking, conversion to Islamic banks.